Gender and geography in Africa: developments, challenges and trajectories for the future - Mariama Awumbila (Documents d'Anàlisi Geogràfica)
This paper provides an overview of current developments in the study of women and gender studies in general and in geography in particular in Africa. It begins by locating gender and women’s studies in the context of international women’s movements and examines the context of gender and women’s studies in Africa. It also traces how gender has evolved and transformed in geography over the decades in sub Saharan Africa and outlines challenges and potential trajectories for future direction on gender and geography in Africa.